Faktor Penentu Pertumbuhan Ekonomi Kabupaten Bungo - Eva Riani; Haryadi Haryadi; Amril Amril (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2014)
This study aims to: (1) analyze the economic growth Bungo district; (2) analyze the factors that affect economic growth Bungo district. The analysis tool used is multiple regression model. Observation data during the period of 2000-2010. The study found that government spending, employment and investment have a significant effect on economic growth Bungo. In contrast, inflation and interest rates showed no significant effect. Keywords: government spending, employment ,investment; inflation; interest rate